Whole-body vibration combined with extra-load training for enhancing the strength and speed of track and field athletes - Wang, H. -H.; Chen, W. -H.; Liu, C.; Yang, W. -W.; Huang, M. -Y.; Shiang, T. Y. (The Journal of Strength and Conditioning Research, 2014)
The purpose of this study was to investigate whether whole-body vibration (WBV) combined with extra-load training can enhance the strength and speed of trained athletes compared with isolated WBV training or loaded training (LT) only. Twenty-one elite male track and field athletes were randomly assigned to a loaded vibration (LV) training group (n = 7), an unloaded vibration (ULV) training group (n = 7), and a LT group (n = 7). During 4 weeks of training, the LV group received the vibration stimulus (30 Hz and 4 mm) accompanied by a load comprising 75% of the maximum voluntary contraction (MVC), the ULV group received the same vibration stimulus without any load, and the LT group received only a load of 75% MVC without any vibration stimulus. The knee extensor isometric strength, and the concentric and eccentric strength were measured using an isokinetic dynamometer at 300°/s at a 30-m sprint speed before and after the training period. A 2-way mixed analysis of variance (time × group) was used to analyze the differences. Significant time × group interactions were observed for all the dependent variables (p < 0.05). Regarding the post hoc analysis results, the LV group exhibited significant improvements for all the dependent variables after training (p < 0.05), whereas the ULV group exhibited significantly reduced sprint speeds (p < 0.05). The LV group demonstrated significantly superior eccentric strength compared with the ULV and LT groups after training (p < 0.05), and the LV group also produced significantly superior sprint speeds compared with the ULV group after training (p < 0.05). Vibration combined with extra-load training for 4 weeks significantly increased the muscle strength and speed of the elite male track and field athletes.